Հայոց Մեծ եղեռնը և Արևմտյան Հայաստանի ժողովրդական արվեստի հուշարձանների ճակատագիրը - Է. Ս. Ավետիսյան (ՀՀ ԳԱԱ հրատ.)
Геноцид армян сопровождался также уничтожением культурных ценностей, являющих собой образцы народного творчества, к числу которых относится церковная утварь из золота, серебра и слоновой кости монастыря Сб. Аствацацин (Св. Богородицы) в Апаране, украшенная резьбой дверь из эбенового дерева монастыря Св. Иоахима и Анны из Евдокии и др. The unity of a nation implies unity of the cultural values it created. Being well aware of it, the Government of Young Turks made part of their massacres the vandalistic destruction of Armenian incomparable cultural values. Thousands of pieces of folk arts were destroyed.
Keywords: History; Armenian Genocide (1915); Geography; Anthropology; Recreation; D History; GCC Culture and Cultural Processes